Lesão por pressão em indivíduos com lesão medular: fatores de risco na reabilitação neurológica - Silva, Janaina Barbosa da (2020)
Objective: to identify risk factors for the occurrence of pressure ulcers in adult individuals with spinal cord injuries in neurological rehabilitation. Methods: integrative review of studies published in the bases Medical Literature Analysis and Retrieval System Online, Cumulative Index to Nursing and Allied Health Literature and Latin American and Caribbean Literature in Health Sciences. Results: 308 studies were found, with six articles selected, based on pre- -established inclusion criteria. The number of risk factors found was similar during and after neurological rehabilitation. Conclusion: the risk factors found for the occurrence of pressure ulcers during and after neurological rehabilitation, were related to sociodemographic conditions, the spinal cord injury itself, associated with clinical condition and behavior. With the exception of complete injury and a history of pressure ulcers, risk factors varied during and after rehabilitation stages.